1999
DOI: 10.1063/1.873668
|View full text |Cite
|
Sign up to set email alerts
|

OEDIPUS-C observations of electrons accelerated by radio frequency fields at whistler-mode frequencies

Abstract: Simultaneous measurements of transmitted 500 kHz electric fields and of electron fluxes nonlinearly energized by those fields were made during the ionospheric flight of the rocket double payload OEDIPUS C. Given the local plasma parameters, 500 kHz corresponded to the whistler mode of cold-plasma propagation. As the separation between each payload end increased from 153 to 537 m, enhanced electron fluxes were detected at energies up to 20 keV, at the receiver end of the tether. Rf (radio frequency) electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…By extension, intense fields were probably created likewise in CMA7 and in the frequency domain of the upper oblique resonance, CMA3. These inferences are merited in the light of observations of sounder-accelerated electrons at all carrier frequencies in CMA3, 7 and 8 [James et al, 1999;Huang et al, 2001], and point to the oblique resonances as having a central role in the RF-acceleration of electrons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By extension, intense fields were probably created likewise in CMA7 and in the frequency domain of the upper oblique resonance, CMA3. These inferences are merited in the light of observations of sounder-accelerated electrons at all carrier frequencies in CMA3, 7 and 8 [James et al, 1999;Huang et al, 2001], and point to the oblique resonances as having a central role in the RF-acceleration of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The reader is referred to previous publications about OC for more detailed descriptions of the principal features of the OC suborbital flight and the operational modes of the HEX-REX combination [James and Calvert, 1998;James et al, 1999].…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…We refer to these emissions as the whistler band [Stix, 1962] based on the frequency relative to the natural gyroand plasma frequencies. This emission is only observed for the same 60 s as the gyrofrequency emissions on the Aft payload [James et al, 1999].…”
Section: Instrumentation and Experimental Backgroundmentioning
confidence: 99%
“…Prior detections of SAEs were made at lower latitudes and involved acceleration of cold ionospheric plasma [James et al, 1999]. By launching into a quiet auroral arc the O-C experiment experienced a background superthermal population superimposed on the cold ambient ionosphere.…”
mentioning
confidence: 99%
“…Three papers have been written analyzing electron plasma responses to the sounder. They have shown that (1) the sounder is capable of accelerating electrons up to the maximum detectable energy of 20 keV ; (2) this acceleration mechanism is largely unexplained by current theories (James et al, 1999); (3) as the rocket descended through the ionosphere a wealth of plasr-.a modes was excited (R. Benson, private communication). Oral pre«": .itations summarizing these results were made at the URSI meeting in Toronto in August 1999.…”
Section: Final Report (1 October 1997 -30 September 2000)mentioning
confidence: 99%